Controllable optical bistability in double quantum dot molecule. Issue 4 (6th June 2018) - Yu, Chunchao; Sun, Lihui; Zhang, Huafeng; Chen, Fang
Abstract : The optical bistability (OB) in the quantum dot molecules with four energy levels in a unidirectional ring cavity has been investigated. The authors find that the OB behaviour in the proposed system can be controlled by the system's different parameters such as electronic cooperation parameter, Rabi frequency of the two coupling laser field, decay rate, three frequency detuning, in which the parameters sensitivity is studied. The proposed system can be used for all optical switching and logic.